Healthcare Costs and Resource Utilization in Patients with Multiple Sclerosis Relapses Treated with H.P. Acthar Gel®. Issue 8 (August 2016) - Gold, Laura; Suh, Kangho; Schepman, Patricia; Damal, Kavitha; Hansen, Ryan
Abstract Introduction Multiple sclerosis (MS) is an autoimmune disorder with large annual costs. This study evaluated utilization and costs for the management of MS relapses with H.P. Acthar® Gel (repository corticotropin injection; Acthar; Mallinckrodt) compared to receipt of plasmapheresis (PMP) or intravenous immunoglobulin (IVIG) among patients with MS who experienced multiple relapses. Methods We identified patients with MS diagnoses who had relapses treated with intravenous methylprednisolone (IVMP), the first-line treatment for MS relapse. Patients who were treated for the subsequent relapses were eligible for the study. We analyzed 12- and 24-month healthcare utilization and costs among patients who received Acthar prescriptions compared to patients who were treated with PMP/IVIG using generalized linear and logistic regression models to calculate unadjusted and adjusted means and 95% confidence intervals. Results For the 12-month analysis, a total of 213 patients received Acthar prescriptions and 226 were treated with PMP or IVIG. Patients who received Acthar prescriptions were similar to those who received other treatments in terms of most demographic variables. Acthar recipients had fewer hospitalizations (0.2 vs. 0.4;P = 0.01) and received fewer outpatient services (29 vs. 43;P < 0.0001) but received more prescription medications (36 vs. 30;P < 0.0001) compared to recipients of PMP/IVIG. Patients who received Acthar prescriptions had lower inpatient and outpatient costs (15, 000 lower;P = 0.001; and 54, 000 lower;P < 0.0001, respectively) but similar total costs. Similar results were seen in the cohort with 24 months of outcome data. Conclusion Acthar may be a useful treatment option compared to PMP/IVIG for patients with MS experiencing multiple relapses. Funding This study was funded by a grant to the University of Washington from Mallinckrodt Pharmaceuticals.